Surviving joy : a novel - Miller, J. P. (James Pinckney), 1919- (D.I. Fine, 1995)
Surviving Joy is the first novel in over ten years by J.P. Miller, the celebrated author of "Days of Wine and Roses," featuring a hugely likeable character whose story, for reasons peculiar to his origins, he feels needs to be told - warts, embarrassments, ecstasies and all - with no holds, literally, barred. It is the story of the early life of Dub Johnson, a.k.a. Tex Frontere, a mannish boy trying to find his way in and about Depression-era Houston, Texas. Dub, who is by turns a brilliant student, eager if naive lover and amateur prize-fighter, is in danger of losing himself in a passion that once seemed to promise the world. Her name is Joy, which is what she gives him - until her consuming desires threaten Dub, his hopes for the future, even his survival.